Recovery of sensory nerve fibres after surgical decompression in lumbar radiculopathy: use of quantitative sensory testing in the exploration of different populations of nerve fibres - Nygaard, O (BMJ Group, 1998)
Thirty nine patients with unilateral lumbar nerve root compression at one level were examined with quantitative sensory testing immediately before microdiscectomy and at six weeks, four months, and 12 months after surgery. Twenty one healthy volounteers were used as controls. The patients were classified as having a good or a poor result at the one year follow up. The improvement of function in small unmyelinated nerve fibres came within six weeks in the patients with a good result. By contrast the improvement of function in small myelinated fibres was not found before 12months after surgery. The function in large myelinated fibres did not improve during the observation period. The difference in the time course of the recovery between large and small nerve fibres is assumed to reflect differing severity in the damage to the fibres before surgical decompression.  The preoperative warmth detection threshold reflecting the function in small unmyelinated C fibres was significantly higher in the patients with a poor result and this may indicate that damage to C fibres before surgery is a negative prognostic factor.